A Multi-Faceted Multi-Stakeholder Approach for Increased Visibility of ETDs in Zambia - Phiri, Lighton (Cadernos BAD, 2020)
The University of Zambia has had a functional Institutional Repository (IR) since 2012. However, while Electronic Theses and Dissertations (ETD) are routinely deposited into the IR, the ingestion is not timely, with significantly large time gaps existing between ETD submission dates and ETD IR ingestion dates. We propose a multi-faceted approach that is aimed at providing a potentially viable solution to the problems through the use of effective workflows and automatic classification of IR objects. Preliminary results demonstrate the potential of the proposed approach is feasible. It is anticipated that the proposed approach will facilitate the implementation of a National ETD portal for storing up-to-date and consistent metadata records from Higher Education Institutions across Zambia.